Investigation on the effect of charge injection from non-thermal plasma on soot formation in laminar coflow diffusion flame - Tan, Yong Ren (2023)
A novel, modified coflow burner was developed to study the effect of charge injection from a non-thermal plasma into three helium-diluted laminar coflow diffusion ethylene flames. The frequency of the high voltage (HV) signal was varied to control the ion concentration (charge) injected into the flames. Optical emission spectroscopy was used to characterize the non-thermal plasma while a bias plate methodology was used to gauge the relative amount of charge generated. For different HV signal frequencies, the laser-induced fluorescence of OH, chemiluminescence of CH*, and laser-induced incandescence of soot in flames were measured. The OH and CH* measurements showed that the flames retained the classic flame shape with charge injection. Significant soot reduction was observed at low HV signal frequencies, corresponding to an increase in charge injection. Notably, at low HV signal frequency, soot reduction in highly concentrated (60%) ethylene flame is three times lower than the less concentrated (32%) ethylene flame. This can be attributed to the decrease in the injected charge to soot precursor concentration ratio when the concentration of ethylene in the flame is increased. These results demonstrate that the current system is a promising candidate for studying the charge effect from non-thermal plasma on soot formation in laminar coflow diffusion flames.